EFEKTIFITAS LITURGI IBADAH DALAM GEREJA PANTEKOSTA ISA ALMASIH KASIH SURGAWI JEMBER - Yusak Noven Susanto (Sekolah Tinggi Teologi Duta Panisal, 2020)
The implementation of worship in a church can run well if it is based on the liturgyarranged and established in a church. Without a liturgy in the church organization, theworship process in the church will not take place. Because there is no measurable andwell-structured system that can manage the worship process. The liturgy of worshipwill bring the church organization to the neatness, regularity and deep appreciation ofGod's presence in the worship process. Seeing the function of worship liturgy that is soimportant and fundamental for church organizations, every church organization musthave a worship liturgy. The method used in the form of a narrative approach, namelyinterviews and documentation. The number of partisipan is 23 people. From all dataobtained through interviews that the definition of worship is the fellowship of the faithin God where that time is a very valuable time because at that time every people canworship, praise, give thanks and hear the very important Word of God. With this resultit is necessary to improve the deficiencies that exist specifically that have a large sectorof praise and worship and sermons.